Deviation of polarity from linearity in liquid mixtures containing an ionic liquid - Beniwal, Vijay; Shukla, Shashi K.; Kumar, Anil (Physical Chemistry Chemical Physics, 2015)
The physico-chemical properties of liquid mixtures, in general, exhibit deviations from linear behaviour with respect to their composition, arising out of different types of cross-intermolecular interactions (both specific and non-specific). These specific and non-specific interactions can however be monitored to obtain the linear mixing in liquid mixtures using the pseudo-solvent methodology in such a manner that the interactions causing deviations from linearity are cancelled out and mixtures display linear behaviour.

Synergistic effects and correlating polarity parameters in binary mixtures of ionic liquids - Beniwal, Vijay; Kumar, Anil (Chemphyschem, 2015)
Understanding how a chemical reaction proceeds in solution requires precise knowledge of solute-solvent interactions. Certain issues involved in ionic liquid binary mixtures are still not clearly understood, including: 1) the effects of hydrogen-bond-acceptor basicity () of solvents on the synergistic effects found in ionic liquid-alcohol mixtures, 2) the interrelation between the polarity parameters in binary mixtures, and 3) the application of a model for the description of normalised electronic transition energy for all the binary mixtures. Here, a detailed analysis of polarity parameters in both hydrophilic and hydrophobic ionic liquids has been carried out. A three-parameter model developed by Roses et al. [J. Chem. Soc. Perkin Trans. 2 1997, 13411348] was found to be applicable to all the binary mixtures, and synergistic effects are generated as a result of high values of alcohols compared with those of the ionic liquids. A strong correlation was observed in the values and hydrophobicities of pure ionic liquids, suggesting that values can play a role in describing synergism.
Keywords: green chemistry; ionic liquids; liquids; noncovalent interactions; solvent effects

Spectacular rate enhancement of the diels-alder reaction at the ionic liquid/n-hexane interface - Beniwal, Vijay; Manna, Arpan; Kumar, Anil (Chemphyschem, 2016)
The use of the ionic liquid/n-hexane interface as a new class of reaction medium for the Diels-Alder reaction gives large rate enhancements of the order of 10(6) to 10(8) times and high stereoselectivity, as compared to homogeneous media. The rate enhancement is attributed to the H-bonding abilities and polarities of the ionic liquids, whereas the hydrophobicity of ionic liquids was considered to be the factor in controlling stereoselectivity.
Keywords: Diels-Alder reaction; Interfaces; ionic liquids; kinetics; stereoselectivity

Understanding positive and negative deviations in polarity of ionic liquid mixtures by pseudo-solvent approach - Beniwal, Vijay; Kumar, Anil (Physical Chemistry Chemical Physics, 2016)
Physico-chemical properties of liquid mixtures in general display large deviations from linear behaviour, arising out of complex specific and non-specific intermolecular interactions. The polarity of liquid mixtures displaying large positive and negative deviations can be minimized and linear mixing can be achieved in liquids using a pseudo-solvent methodology. The work described herein is designed to investigate the influence of different physical parameters on the linear pseudo-solvent composition in ionic liquid mixtures. For this purpose, we have determined the deviations from linearity, Delta E-T(N) values (defined as Delta E-T(N) = E-Texp.(N) - E-Tlin mix.(N) with E-Tlin mix.(N) given by Sigma(n)(i=0) E-Ti(N0) x(i)) for binary mixtures of a variety of ionic liquids, including two molecular solvents, DMSO and formamide. Firstly, the investigations were carried out in three 1-butyl-3-methylimidazolium cation based aprotic ionic liquids and the roles of anionic structure and hydrogen bond acceptor basicities (beta values) of the ionic liquids were determined. The influence of the cationic structure, i.e., the hydrogen bond donor acidity (alpha values) and non-associative nature of the ionic liquids, was determined using C2-methylated analogs, 1-butyl-2,3-dimethylimidazolium cation based ionic liquids. The role of the protic nature of ionic liquids was studied in two protic ionic liquids, viz., 1-methylimidazolium formate and 1-methylimidazolium acetate. The effects of the temperature, pseudo-solvent structure and solvatochromic probe structure on the Delta E-T(N) values were also explored.

Introducing the bipolar solvent media using the aqueous mixtures of amino acid anion-based ionic liquids - Beniwal, Vijay; Kumar, Anil (Journal of Physical Chemistry B, 2017)
To carry out a chemical reaction between the reactants with largely different polarities, it becomes important to have a reaction medium that possesses both the polar and nonpolar solvation environments. In an attempt to explore the reaction media with such unique polarity properties, the present study provides a thorough understanding of the bipolar solvent media using the aqueous mixtures of amino acid anion-based ionic liquids. The highly polar behavior of the binary mixtures used in the study has been ascribed to the pure ionic liquid state. However, the less polar solvation shells have been attributed to the presence of a neutral form of the anions. Addition of water in the amino acid anion-based ionic liquids causes the protonation of a certain fraction of the anions of the ionic liquids, resulting into the formation of a less polar nonionic protonated form along with the highly polar natural anionic form. This results into the formation of two solvation spheres with different polarities, which can be seen very clearly from the presence of two absorption bands (lower wavelength absorption band and higher wavelength absorption band) in the UV-vis absorption spectrum of Reichardt's E-T(30) dye and two emission bands (lower wavelength emission band and higher wavelength emission band) in the fluorescence emission spectrum of C481 dye. The values of the E-T(N) polarity parameter corresponding to the two solvation shells having different polarities have been calculated from the deconvoluted absorption spectra of the Reichardt's E-T(30) and were analyzed in three amino acid anion-based ionic liquids. Generation of the neutral form of anions in the aqueous mixtures formed via a protonation transfer reaction has been confirmed by the H-1 NMR spectroscopy and UV-vis absorption spectrum of 18DHAQ dye. The study also establishes that the Reichardt's E-T(30) dye can be used as a valid polarity probe to study the solvatochromic behavior of the binary mixtures of amino acid-based ionic liquids.

Thermodynamic and molecular origin of interfacial rate enhancements and endo-selectivities of a Diels-Alder reaction - Beniwal, Vijay; Kumar, Anil (Physical Chemistry Chemical Physics, 2017)
Organic reactions in general display large rate accelerations when performed under interfacial conditions, such as on water or at ionic liquid interfaces. However, a clear picture of the physicochemical factors responsible for this large rate enhancements is not available. To gain an understanding of the thermodynamic and molecular origin of these large rate enhancements, we performed a Diels-Alder reaction between cyclopentadiene and methyl acrylate at ionic liquid/n-hexane interfaces. This study describes, for the first time, a methodology for the calculation of the activation parameters of an interfacial reaction. It has been seen that the energy of activation for an interfacial reaction is much smaller than that of the corresponding homogeneous reaction, resulting into the large rate acceleration for the interfacial reaction. Furthermore, the study describes the effects of the alkyl chain length of ionic liquid cations, the extent of heterogeneity, and the polarity of ionic liquids on the rate constants and stereoselectivity of the reaction.

Excited state intramolecular proton transfer in 1,8-Dihydroxy-9,10-anthraquinone dye: Revealing microstructures in [C(n)mIm][NTf2] and [C(n)mIm][BF4] series of ionic liquid solvents - Beniwal, Vijay; Kumar, Anil; Pal, Haridas (Journal of Photochemistry and Photobiology A-Chemistry, 2018)
Excited state intramolecular proton transfer (ESIPT) in 18-dihydroxy-9,10-anthraquinone (18DHAQ) dye has been investigated in two series of 1-alkyl-3-methylimidazolium ([C(n)mIm](+)) based ionic liquid (IL) solvents, [C(n)mlm][NTf2] and [C(n)mlm][BF4], with n = 2, 4, 6, 8 and 10, using steady-state (SS) and time resolved (TR) fluorescence studies. In both the IL series, fluorescence intensity for tautomer (T*) form gradually decreases relative to normal (N*) form with increasing n value for [C(n)mlm](+) cations. Observed results suggest microstructure formation and its consequent effect on the ESIPT process of the dye in these IL solvents. Since more extensive microstructures are likely with larger n values of [C(n)mIm](+) cations, the dye is expectedly solubilized more in the polar microdomains of the solvent microstructures, resulting better stabilization for the more dipolar N* state and hence a higher emission intensity from this state. This proposition is clearly supported by ultrafast (sub-picosecond) fluorescence kinetics for both N* and T* states, though sub-nanosecond TR results indicate very similar fluoresce decays for both N* and T*, suggesting an eventual kinetic equilibrium between two states subsequent to the initial ultrafast and fast forward and backward ESIPT processes. Small differences between the results in the [C(n)mIm][NTf2] and [C(n)mIm][BE4] series of ILs are attributed to dissimilar size, shape and basicity of [NTf2]- and [BF4]- anions, responsible for some characteristic changes in the microstructures formed in the respective solvent series. To the best of our knowledge, present study is the only report demonstrating modulations in the ESIPT process through microstructure formations in neat [C(n)mIm](+) based IL solvents. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 1; 1-Alkyl-3-methylimidazolium ionic liquids; 8-Dihydroxyanthraquinone; Emission modulations of tautomeric forms; ESIPT process; Microstructure formation

Excited-state prototropism of 7-hydroxy-4-methylcoumarin in [C(n)mim][BF4] series of ionic liquid-water mixtures: insights on reverse micelle-like water nanocluster formation - Beniwal, Vijay; Kumar, Anil; Pal, Haridas; Choudhury, Sharmistha Dutta (Photochemical & Photobiological Sciences, 2018)
This study explores the excited state prototropic behavior of the fluorophore, 7-hydroxy-4-methylcoumarin (7H4MC), in the [C(n)mim][BF4] (n = 2, 4, 6, 8, 10) series of ionic liquid (IL)-water mixtures at low water contents. In pure IL media, 7H4MC exists in the neutral form in both ground and excited states. However, on addition of water to the ILs, the excited neutral form of the dye is gradually converted to the anionic and the tautomeric species, leading to characteristic changes in the emission spectra. The similarity in the spectral features of 7H4MC in the IL-water system with that in a conventional reverse micelle system rather than with organic solvent-water mixtures, suggests that in the presence of water, the ILs are organized into reverse micelle-like structures with the consequent formation of confined water pockets. The results further suggest that formation of water nanoclusters and the ensuing changes in excited state prototropic behavior of the dye, is facilitated by increase in the alkyl chain length of the IL cation. These propositions are supported by time-resolved fluorescence studies. To the best of our knowledge this is the first report on proton transfer reaction in IL-water mixtures at low water contents. Considering that ILs are useful as solvents and surfactants, and IL-water mixtures in particular have applications in chemical extractions and biocatalysis, an understanding of the structural organization and water pool formation in these systems is quite important. The insights obtained from the prototropic transformations of 7H4MC are significant not only for fundamental self-assembly studies, but also for the development of ILs as chemical reaction media.